Communicating for Impact: Finding the story in your research - Mulvey, Laura; Kashef, Shayda; Gordon, Emma (International Journal of Population Data Science, 2024)
Researchers who wish to make an impact need to capture people’s attention and inspire action. But to people outside the sector, population data research can be hard to relate to. Better communication can help us overcome this barrier. The objective of this workshop was to explore how researchers can communicate more effectively, to encourage engagement, demonstrate trustworthiness and achieve real-world impact. It aimed to build participants’ skills and confidence in sharing their research, including: selecting key messages to resonate with different audiences building a compelling story techniques for accessible communication. The approach taken was a mixture of presentations, group discussions and activities. The session began with icebreaker exercises and a discussion on the importance and benefits of effective research communication – for the public, policymakers, and researchers themselves. The group then moved on to explore how researchers can identify the different audiences they want to reach. Small groups were given fictional user personas, and tasked with developing a suitable user need statement and key message for them, based on an existing piece of research. The central discussion of the workshop focused on the key elements that make up a compelling story, how these might map onto a piece of data research, and how these elements can be arranged to engage different audiences. Participants took part in a planning exercise to develop a research story. The workshop concluded with tips for accessible communication, and some reflection.